Dzieło muzyczne jako droga do doświadczeń transcendentnych lub mistycznych. Perspektywa filozoficzna - Trzciński, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
This article aims to investigate the relationship between musical works and transcendental or mystical experiences among listeners. The analysis was conducted within the context of philosophical research. The first part of the text focuses on exploring concepts such as mystical and transcendental experiences. Subsequently, historical conceptions describing the relationships between music and these experiences are presented. In this context, the views of prominent philosophers such as Plato, Hegel, Schopenhauer, Nietzsche, Langer, Gadamer, and Jankélévitch are discussed. The article also includes a discussion on philosophical concepts that highlight specific aspects of music capable of inducing transcendental or mystical experiences, including artistic expression, the aesthetics of the work, and its ethical implications.
The Musical Work as a Path to Transcendental or Mystical Experiences: A Philosophical Perspective
Keywords: Music; Musical work; mysticism; mystical experiences; transcendent experiences